Dynamic in vitro culture of cryopreserved-thawed human ovarian cortical tissue using a microfluidics platform does not improve early folliculogenesis - Del Valle, Julieta S.; Mancini, Vanessa; Laverde Garay, Maitane; Asseler, Joyce D.; Fan, Xueying; Metzemaekers, Jeroen; Louwe, Leoni A.; Pilgram, Gonneke S. K.; Westerlaken, Lucette A. J. van der; van Mello, Norah M.; Chuva de Sousa Lopes, Susana M. (Frontiers in Endocrinology, 2022)
Current strategies for fertility preservation include the cryopreservation of embryos, mature oocytes or ovarian cortical tissue for autologous transplantation. However, not all patients that could benefit from fertility preservation can use the currently available technology. In this regard, obtaining functional mature oocytes from ovarian cortical tissue in vitro would represent a major breakthrough in fertility preservation as well as in human medically assisted reproduction. In this study, we have used a microfluidics platform to culture cryopreserved-thawed human cortical tissue for a period of 8 days and evaluated the effect of two different flow rates in follicular activation and growth. The results showed that this dynamic system supported follicular development up to the secondary stage within 8 days, albeit with low efficiency. Surprisingly, the stromal cells in the ovarian cortical tissue were highly sensitive to flow and showed high levels of apoptosis when cultured under high flow rate. Moreover, after 8 days in culture, the stromal compartment showed increase levels of collagen deposition, in particular in static culture. Although microfluidics dynamic platforms have great potential to simulate tissue-level physiology, this system still needs optimization to meet the requirements for an efficient in vitro early follicular growth.